Epidemiology of children and adolescents referred to a gender violence reference team during the COVID-19 pandemic as compared to 2016.: CASMU-IAMPP (Archives of Pediatrics of Uruguay, 2022)
Child and sexual abuse involve a breach of human rights and a major global health problem. The situation was already serious and complex before the Covid 19 Pandemic, but it has turned it into a crisis. In March 2020, preventive measures were taken to mitigate the effects of the disease, the lockdown was one of them. Child abuse rose from 20% to 32% in 2020.Objective: learn about the epidemiological characteristics of children and adolescent victims of abuse and probable sexual abuse, assisted by the Gender Based Violence Reference Team at one institution, between April 1, 2020 and 31 July 2020, compared to the same period in 2016.An observational, descriptive study was carried out with users under 18 years of age referred to team mentioned above.The total number of consultations was 28 in 2016, and 17 in 2020. The reasons for consultation in 2016 were: 24.5% sexual abuse, 3.5% neglect and 72% emotional abuse within the framework of domestic violence. In 2020 they were 41%, 6% and 53%, respectively. In 2016, 82% of the cases were referred by the health sector, 36% of them by the treating pediatrician. In 2020 76% and 46%, respectively. Despite the multiple global reports and publications that suggest a state of emergency for the case of children and adolescents due to the Covid-19 pandemic, this was not reflected in our figures.
Keywords: Child sexual abuse; Child abuse; Domestic violence; COVID-19; SARS-CoV-2